Framing Analysis of News About Damaged Roads in East Cirebon Regency on Cirebon People's Online Media for the Period of April 2025 - Fiqri, Dede; Risnawati, Ririn; Kamaluddin, M.; Sapari, Yusuf; Machsunah, Uun (Jurnal Polisci, 2026)
Background. In the contemporary communication landscape, online media has transformed into a central pillar in the dissemination of information and the formation of public opinion. The speed, accessibility, and global reach of digital platforms enable news and information to spread instantly, transcending geographical and temporal constraints. Aims. This study aims to analyze how the local media outlet Rakyat Cirebon framed news coverage of damaged roads in East Cirebon Regency during April 2025. The issue of road infrastructure gained public attention due to its significant impact on residents' daily lives and economic activities. Methods. Using a qualitative approach and the framing analysis model developed by Robert N. Entman, this research explores how the media selects, emphasizes, and structures information to shape particular meanings in its audience's minds. Result. The findings reveal that Rakyat Cirebon consistently framed road damage as a failure of the local government to respond to public needs. The four framing elements—problem definition, causal interpretation, moral evaluation, and treatment recommendation—indicate a strong narrative that criticizes the executive branch while portraying the regional legislature (DPRD) as an active defender of public interests. Visual strategies, including emotive photographs, dramatic language, and selective sourcing, further reinforce the dominant frame presented. Conclusion. This study highlights that media framing is not merely a reflection of social reality, but an active process of constructing that reality through deliberate editorial choices. As such, media outlets hold an ethical responsibility to provide balanced and accurate reporting. Implementation. The findings also underline the importance of media literacy among the public, enabling citizens to engage critically with the narratives constructed by the press. On the other hand, local governments must be more proactive and transparent in addressing public issues in the media.